Women, Labor Segmentation and Regulation : Varieties of Gender Gaps - Peetz, David; Murray, Georgina (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This book re-shapes thinking on 'gender gaps'-differences between men and women in their incomes, their employment and their conditions of work. It shows how the interaction between regulation distance and content, labor segmentation and norms helps us understand various aspects of gender gaps. It brings together leading authors from industrial relations, sociology, politics, and feminist economics, who outline the roles the family, state public policy, trade unions and class play in creating gender gaps, and consider the lessons from international comparisons. While many studies have focused on the role of society or organizations, this book also pays attention to the role of occupations in promoting and reinforcing gender gaps, discussing groups such as apparel outworkers, film and video workers, care workers, public-sector professionals like librarians, chief executives, academics, and coal miners. This book will be of interest to practitioners, policy makers, academics and students interested in understanding why inequality between men and women persists today-and what might be done about it.- Resumé vydavatel
Keywords: rovné postavení mužů a žen; diskriminace v zaměstnání; gender equality; discrimination in employment; elektronické knihy; kolektivní monografie; electronic books; collective monographs